2004
DOI: 10.1097/00005537-200404000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Reactive Oxygen Species in Myringotomized Tympanic Membranes: Effect of Vitamin E Treatment

Abstract: Although the relationship between the development of myringosclerosis and ROS had been well documented previously, the present study is the first that has directly measured the levels of ROS in the tympanic membrane and middle ear mucosa. These results are relevant because they correlate with histological findings. It has also been demonstrated that topically applied vitamin E is effective in decreasing the ROS levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 38 publications
1
39
1
Order By: Relevance
“…Previous studies in literature have demonstrated that the use of vitamin E, ascorbic acid, selenium, N-acetylcysteine, L-carnitine can prevent the development of myringosclerosis [5,8,10,17] .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies in literature have demonstrated that the use of vitamin E, ascorbic acid, selenium, N-acetylcysteine, L-carnitine can prevent the development of myringosclerosis [5,8,10,17] .…”
Section: Discussionmentioning
confidence: 98%
“…As a striking finding, as for the structure and location of plaques, microscopic examination of sclerotic lesions reveals no difference between rats and human beings [15,16] . Another issue to be underlined is that irreversible tissue damage induced by free oxygen radicals is the most important factor in the development of myringosclerosis [5,8,10,17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polat et al (22) concluded that inflammatory reactive oxygen species increased due to the immunological stimulation in the formation of tympanosclerosis after myringotomy and vitamin E reduced this effect. Selçuk et al (23) emphasized that the application of topical calcium channel blocker in guinea pigs on experimental myringosclerosis, which they created with myringotomy and Streptococcus pneumoniae type 3 inoculation, helped prevent tympanosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The conditions that damage the integrity of the middle ear, such as myringotomy, cause the oxygen concentration to rise to 21% by causing the ambient air to pass into the middle ear cavity [18] . Previous studies have shown that an increased oxygen concentration causes the development of myringosclerosis by increasing the production of oxygen free radicals [19,20] .…”
Section: Discussionmentioning
confidence: 99%